0109 Working Memory across Sleep and the Menstrual Cycle in Young and Midlife Women. (25th May 2022) - Shuster, Alessandra; Zhang, Jing; Sattari, Negin; Simon, Katharine; Alzueta, Elisabet; Dulai, Teji; de Zambotti, Massimiliano; Baker, Fiona; Mednick, Sara
Abstract: Introduction: The menses phase of a woman's menstrual cycle, compared to other phases, is more likely to be associated with poorer sleep quality and alterations in cognitive performance, specifically impaired working memory. However, the relationship among these factors has been poorly investigated, and how age impacts these relationships is currently unknown. The present study examines the effect of menstrual cycle phase and sleep on working memory performance in young and midlife women. Methods: Fifty-five young and midlife women (n = 29, 18 – 35 years; n = 26, 45 – 56 years) completed four remote assessments at different phases of their menstrual cycle: menses, late-follicular, mid-luteal, and late-luteal, defined based on days of menses and ovulation. On each visit, participants completed the operation span (OSPAN) working memory task in the evening and were re-tested for sleep-related performance change in the morning. In addition, participants wore an Oura ring, a multi-sensor wearable sleep tracker, throughout the night. Mixed linear regression, correlation models, and paired t-tests were used to determine the relationship between menstrual phase, sleep, and OSPAN outcomes in both groups. Results: In midlife women only, OSPAN performance improvement significantly changed across menstrual cycle phases (p < .05). The greatest post-sleep improvement in OSPAN performance was detected during the mid-luteal and late-follicular phases of the cycle, while lower performance gains were detected during menses and late-luteal phases. Post-hoc paired t-tests confirmed that post-sleep performance was significantly worst during menses compared to each of the other phases (p < .05). Additionally, during the mid-luteal phase, time spent in deep sleep positively correlated with post-sleep performance in midlife women (r = .55, p < .05). No significant effects were detected in young women. Conclusion: These findings suggest a complex interaction between sleep, menstrual cycle phase, and cognitive performance in midlife women. Our data suggest that deep sleep may mediate post-sleep performance during specific cycle phases. Reasons why these results are not evident in younger women are yet to be determined. Support (If Any): Supported by: RF1AG061355 (Baker/Mednick)